2016
DOI: 10.5039/agraria.v11i1a5356
|View full text |Cite
|
Sign up to set email alerts
|

Propágulos e formação de micorriza em taludes de rodovia, no sul de Minas Gerais, Brasil

Abstract: RESUMOÁreas de taludes sofrem impactos em função do corte do solo em profundidade, dificultando sua revegetação. Entretanto, mesmo com limitações físicas e químicas da qualidade do solo, é observado o crescimento e/ou sobrevivência de espécies vegetais. Os solos de talude, além da baixa fertilidade, ainda são, normalmente, erodidos. Para esses casos, os microrganismos, como os fungos micorrízicos arbusculares, podem contribuir para aumentar a disponibilidade de nutrientes para as plantas e agregação do solo, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…This marked variation in DS is mainly related to the climatic condition, soil, rainfall, and cultural treatments applied to the study areas. MELLONI et al (2016) confirmed that DS usually shows a marked variation in cultivated soils because AMF spores are affected by several biotic and abiotic factors. LIMA et al (2013) and JIMÉNEZ-LEYVA et al (2017) confirmed that the DS in the rhizosphere is variable and is related to root distribution, morphology, and age, in addition to other factors including soil chemical characteristics (particularly P content), regional rainfall, and AMF species.…”
Section: Resultssupporting
confidence: 53%
“…This marked variation in DS is mainly related to the climatic condition, soil, rainfall, and cultural treatments applied to the study areas. MELLONI et al (2016) confirmed that DS usually shows a marked variation in cultivated soils because AMF spores are affected by several biotic and abiotic factors. LIMA et al (2013) and JIMÉNEZ-LEYVA et al (2017) confirmed that the DS in the rhizosphere is variable and is related to root distribution, morphology, and age, in addition to other factors including soil chemical characteristics (particularly P content), regional rainfall, and AMF species.…”
Section: Resultssupporting
confidence: 53%